2003
DOI: 10.1111/1467-9450.00320
|View full text |Cite
|
Sign up to set email alerts
|

Episodic and semantic memory in bilingual and monolingual children

Abstract: Although bilinguality has been reported to confer advantages upon children with respect to various cognitive abilities, much less is known about the relation between memory and bilinguality. In this study, 60 (30 girls and 30 boys) bilingual and 60 (30 girls and 30 boys) monolingual children in three age groups (mean ages 8.5, 10.5 and 12.5 years) were compared on episodic memory and semantic memory tasks. Episodic memory was assessed using subject-performed tasks (with real or imaginary objects) and verbal ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 44 publications
7
54
6
Order By: Relevance
“…The enactment effect for SPTs (i.e., the difference between SPT and VT) was systematically increased across school ages under all test conditions, and the development of an enactment effect for EPTs (i.e., the difference between EPT and VT) was less or unobservable or absent under different test conditions. Consistent with previous studies (e.g., Kormi-Nouri, 1995Kormi-Nouri et al, 2003), these findings demonstrate that SPT encoding is strategic and affected by developmental differences. This contrasts with the nonstrategic view of SPT encoding proposed by Cohen (1981Cohen ( /1983Cohen ( /1989).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The enactment effect for SPTs (i.e., the difference between SPT and VT) was systematically increased across school ages under all test conditions, and the development of an enactment effect for EPTs (i.e., the difference between EPT and VT) was less or unobservable or absent under different test conditions. Consistent with previous studies (e.g., Kormi-Nouri, 1995Kormi-Nouri et al, 2003), these findings demonstrate that SPT encoding is strategic and affected by developmental differences. This contrasts with the nonstrategic view of SPT encoding proposed by Cohen (1981Cohen ( /1983Cohen ( /1989).…”
Section: Discussionsupporting
confidence: 91%
“…Cohen's study is one of the few experimental investigations that did not identify developmental differences in action memory performance. In contrast to Cohen's study, other researchers have identified memory enhancement with age; older children exhibit a larger enactment effect than younger children (e.g., Kormi-Nouri, Moniri, & Nilsson, 2003;KormiNouri et al, 2008). These studies stress the importance of strategy use in action items, especially when elementary school students are instructed to interact physically with objects during learning.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Likewise, bilingual children in grades 3, 8, and 11 performed better on episodic memory tasks involving recognition and recalled significantly more on subject performed tasks compared with monolingual control subjects (Kormi-Nouri, Moniri, & Nilsson, 2003). This advantage seems more pronounced in older children, which may help to explain why enhanced memory was not observed in the majority of studies because participants in other studies ranged from preschool to second grade.…”
Section: Memorymentioning
confidence: 93%
“…According to the revised hierarchical model (Kroll and Stewart, 1994; Kroll et al, 2010), lexical connections between the two languages in bilinguals are linked to common conceptual memory representations; and the connections to conceptual memory depend on bilinguals' L1 and L2 experiences and knowledge. In the same vein, evidence regarding bilinguals' language knowledge in two languages, bilinguals' episodic memory, and their semantic memory (e.g., Francis, 1999; Kormi-Nouri et al, 2003, 2008, 2012; Sheng et al, 2006, 2013; Bialystok and Feng, 2009) suggests that bilinguals differ from monolinguals in how they encode, retain, and organize words.…”
Section: Introductionmentioning
confidence: 99%